Bibliometric Analysis: Emotional Intelligence on Leadership - Permana, Yudha Aviv; Mahendra, Yudhistira Ihza (Banking & Management Review, 2025)
Introduction/Main Objectives: This study explores research trends on Emotional Intelligence (EI) within transformational leadership. As EI increasingly emerges as a critical competency for effective leadership in dynamic organizational settings, examining its scholarly development is essential. Background Problems: Despite extensive EI research across disciplines, its integration into transformational leadership remains fragmented. Limited understanding persists regarding how EI supports leadership development across cultural and institutional contexts. This study addresses these gaps by analyzing global research trends and directions of EI within transformational leadership. Novelty: This paper presents a comprehensive bibliometric review mapping the global landscape of EI-related studies in leadership. It highlights underexplored dimensions such as cultural diversity, digital work environments, and leadership development programs—areas often overlooked in previous studies. Research Methods: Using the Scopus database, 1,428 documents were retrieved with the keyword “Emotional Intelligence,” restricted to the Business, Management, and Accounting field. Bibliometric analysis with VOSviewer examined co-authorship, keyword co-occurrence, publication trends, and geographical distribution. Finding/Results: Publications on EI have grown steadily between 1999 and 2024, peaking during 2005–2010 and 2016–2024. Thematic links connect EI with emotional regulation, motivation, empowerment, and innovation. The United States, United Kingdom, and Australia were identified as leading contributors, with influential scholars including Neal M. Ashkanasy and Ronald H. Humphrey. Conclusion: The findings reaffirm EI’s critical role in transformational leadership and highlight the need for further exploration in cross-cultural and digital contexts. The study offers insights for developing emotionally intelligent leadership frameworks to enhance adaptability and organizational performance.